2011
DOI: 10.1021/ma2015358
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in PEO–PPO–PEO Gels Induced by Methylparaben and Dexamethasone Observed Using Time-Resolved SAXS

Abstract: Aqueous solutions of polyoxyethylene–polyoxypropylene–polyoxyethylene (PEO–PPO–PEO) triblock copolymers (commercially available as Pluronic surfactants) micellize and structurally arrange into cubic quasicrystalline lattices as their temperature is raised. This structural evolution is seen macroscopically as a gelation, and the presence of these ordered phases can be controlled through both polymer concentration and temperature. The presence of added solutes within the dispersions can also affect the onset and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
4
27
0
Order By: Relevance
“…S8 in ESI. The relative positions of the peaks show a face centered cubic structure (FCC) for F127 gel in agreement with the literature [40]. Pure 25% L64 exhibits only a broad peak characteristic of a disordered system because it never forms a gel at any temperature.…”
Section: Gelation and Rheologysupporting
confidence: 89%
See 2 more Smart Citations
“…S8 in ESI. The relative positions of the peaks show a face centered cubic structure (FCC) for F127 gel in agreement with the literature [40]. Pure 25% L64 exhibits only a broad peak characteristic of a disordered system because it never forms a gel at any temperature.…”
Section: Gelation and Rheologysupporting
confidence: 89%
“…We note that the fundamental peak (q 0 ) could not be seen for pure F127 at certain temperatures (not shown). This problem has also been reported previously for similar systems [40,41], but the exact cause is not fully understood. Fig.…”
Section: Gelation and Rheologysupporting
confidence: 64%
See 1 more Smart Citation
“…-TTBP-Pluronic hydrogels before and after the annealing.I th as been reported that 30 wt %P luronic F127based hydrogels show SAXS peaks at 0.39 and 0.45 nm À1 , which become stronger after heat treatment and have been assigned to the micelle assemblies with fcc order. [12] Both of the Os(peptpy) 2 2+ -TTBP-Pluronic hydrogels without/with…”
Section: +mentioning
confidence: 99%
“…It has also been shown that the CMC or CMT for a polymer depends on its molecular weight (PEO/PPO block length) and PEO (hydrophilic)-PPO (hydrophobic) content ratio (Deng, Yu, Price, & Booth, 1992;Price, 1983). This structural organization macroscopically leads to gelation (Meznarich, Juggernauth, Batzli, & Love, 2011;. By altering these parameters, the polymer properties can be finely tuned.…”
Section: Poly(ethylene Oxide)-poly(propylene Oxide)poly(ethylene Oxidmentioning
confidence: 99%